The impact of climate litigation risk on firms' cost of bank loans - Andreas Beyer; Lorenzo Nobile (European Central Bank (ECB), 2025)
Using a novel worldwide dataset of 5,264 syndicated loans issued to 329 firms from 2006 to 2021, we study how climate-related litigation risk affects firm's cost of borrowing. We find robust empirical evidence that firms targeted by climate lawsuits pay significantly higher spreads on their bank loans. These effects are more pronounced for firms with weaker environmental performance and higher ESG controversies. The results suggest that lender's view climate litigation as a material risk factor, which is increasingly priced into debt contracts.
Keywords: G21; G32; Q56; K32; 330; climate lawsuits; bank loans; loan spreads; litigation risk